2019 Trade finance gaps, growth, and jobs survey. - Kim, Kijin (Metro Manila, Philippines Asian Development Bank, 2019)
This years survey found that the global trade finance gap remains at around 1.5 trillion, nearly 60% of respondents expect the gap to increase over the next 2 years. Another key finding was that women owned firms face greater challenges accessing trade finance than do men-owned firms. Meanwhile, small and medium sized enterprises (SMEs) also face considerable barriers with more than 40% of SME trade finance applications rejected by banks. However there is growing optimism that fintech and digitization are potential solutions to bridge the trade finance gap, particularly for SMEs.
Keywords: Small business -- Asia -- Finance; Service industries -- Asia; Electronic books